Porcine ubiquitin-like 5 (UBL5) gene: genomic organization, polymorphisms, mRNA cloning, splicing variants and association study - Masopust, Martin; Weisz, Filip; Bartenschlager, Heinz; Knoll, Aleš; Vykoukalová, Zuzana; Geldermann, Hermann; Cepica, Stanislav (Molecular biology reports, 2014)
Ubiquitin-like 5 (UBL5), which is supposed to be involved in regulation of feed intake, energy metabolism, obesity and type 2 diabetes, is located at position 62.1 cM on the pig chromosome 2 region harbouring quantitative trait loci for carcass and meat quality. The 4,354 bp genomic sequence (FR798948) of the porcine gene encompassing the promoter and entire gene was cloned by polymerase chain reaction. Comparative sequencing revealed 13 polymorphisms in noncoding regions. Synthesis of full-length cDNA sequences using rapid amplification of 5' and 3' ends showed three splice variants. Variants 1 and 2 differ in transcription length for the untranslated part of exon 1 with deduced protein of 73 amino acid (aa) residues and 100 % identities between human, mouse and other species. Variant 3, with 4 bp deletion at the 3' end of exon 2, encodes a truncated protein with 28 aa residues. In a Wild boar×Meishan F2 population (n = 334) with 47 recorded traits, loci FR798948:g.2788G>A and FR798948:g.2141T>C were associated at nominal P < 0.05 with fat deposition, growth and fattening and muscling but after adjustment for multiple testing (Benjamini and Hochberg, J R Stat Soc B 57:289-300, 1995) only eight fat deposition traits showed suggestive association with FR798948:g.2788G>A at adjusted P < 0.10. In a Meishan×Large White (MLW) cross (n = 562) with six trait records available, FR798948:g.2141T>C showed suggestive association with growth (adjusted P = 0.0690). As association mapping conducted in the outbred MLW population is more precise than in the three generation F2 population the UBL5 gene tends to be associated with growth rather than with fat accretion.
Keywords: klonování DNA; zvířata; Male; Gene Order; Swine; prasata; pořadí genů; RNA, Messenger; messenger RNA; Animals; Ubiquitins; promotorové oblasti (genetika); polymorfismus genetický; ženské pohlaví; genom; genetické asociační studie; sestřih RNA; RNA Splicing; Genome; Genetic Association Studies; Cloning, Molecular; Female; Promoter Regions, Genetic; Polymorphism, Genetic; mužské pohlaví; ubikvitiny